2005
DOI: 10.1097/01.mlg.0000176540.33486.c3
|View full text |Cite
|
Sign up to set email alerts
|

Level IIb Lymph Nodes Metastasis in Elective Supraomohyoid Neck Dissection for Oral Cavity Squamous Cell Carcinoma: A Molecular‐Based Study

Abstract: In this study, level IIb lymph node metastasis was only found in association with tongue carcinoma. Although this region may be preserved in elective SOHND in patients with SCC of the oral cavity, it should be included whenever the tongue is the primary site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 21 publications
2
44
1
Order By: Relevance
“…There was no instance of isolated or contralateral metastases at level IIb. This was in accordance with results of other authors [15,16,17] . Palleri et al in their prospective study of 50 patients found a positivity at level IIb in 3.9 % oral cavity cancers with contralateral (0.9 %) and isolated (0.3 %) metastases being extremely rare.…”
Section: Discussionsupporting
confidence: 83%
“…There was no instance of isolated or contralateral metastases at level IIb. This was in accordance with results of other authors [15,16,17] . Palleri et al in their prospective study of 50 patients found a positivity at level IIb in 3.9 % oral cavity cancers with contralateral (0.9 %) and isolated (0.3 %) metastases being extremely rare.…”
Section: Discussionsupporting
confidence: 83%
“…It has been demonstrated that isolated level IIB metastases from oral cavity cancers are exteremely rare (Lea, 2010). But, when other levels, especially level IIA, contain occult metastases, level IIB metastases may occur in up to 22% of the patients (Elsheikh, 2005, Lea, 2010. Interestingly, level IIB metastases are almost always seen in patients with tongue cancer, however other oral cavity primary sites only rarely give rise to level IIB metastases (Elsheikh, 2005, Lea, 2010.…”
Section: Extent Of Surgical Removal For Selective Neck Dissectionmentioning
confidence: 99%
“…But, when other levels, especially level IIA, contain occult metastases, level IIB metastases may occur in up to 22% of the patients (Elsheikh, 2005, Lea, 2010. Interestingly, level IIB metastases are almost always seen in patients with tongue cancer, however other oral cavity primary sites only rarely give rise to level IIB metastases (Elsheikh, 2005, Lea, 2010. When the lesion is located in the retromolar trigone with extension to the anterior pillar, level IIB should be dissected (Ayad, 2009).…”
Section: Extent Of Surgical Removal For Selective Neck Dissectionmentioning
confidence: 99%
“…Initially, this procedure was used in necks with no metastatic lymph nodes (cN0) and in those cases with lymph node metastases up to 2 cm with no rupture of the capsule (pN1). [9][10][11][12][13][14][15][16][17] These studies underlined our proposition to change the extension of neck dissection for the surgical treatment of necks with clinical metastases (cN1) from squamous cell carcinoma in the lower region of the mouth. We based our proposition on the follow-up of patients and the diagnosis of lymph node recurrence in those anatomical regions not included in the selective procedure.…”
Section: Introductionmentioning
confidence: 99%